Highly efficient gene release in spatiotemporal precision approached by light and pH dual responsive copolymers. Issue 1 (17th October 2018) - Lu, Hung-Hsun; Huang, Cheng-Hung; Shiue, Ting-Yun; Wang, Fu-Sheng; Chang, Ko-Kai; Chen, Yunching; Peng, Chi-How
Abstract : Triblock copolymer, PEG- b -PDMAEMA- b -PPy, has been shown as an ideal carrier with remarkable siRNA condensation, high stability, efficient gene release, and negligible cytotoxicity for gene delivery. Abstract : Triblock copolymer of poly(ethylene glycol)- b -poly(2-dimethylaminoethyl methacrylate)- b -poly(pyrenylmethyl methacrylate) (PEG- b -PDMAEMA- b -PPy) has been developed for use as an ideal gene delivery system, which showed both high stability under physiological conditions and efficient gene release in a mimetic cancer environment. The siRNA release from this system without external stimulation was 16% in 1 h and then remained steady. However, the photo-triggered siRNA release was 78% within 1 h and was higher than 91% after 24 h. The remarkable contrast between the stability and release efficiency of these siRNA-condensed micelleplexes before and after photo-irradiation has been rationalized by the light- and pH-induced structural transitions of the triblock copolymer micelles. The negligible cytotoxicity, high cellular uptake efficiency, and remarkable knockdown efficiency shown in in vitro tests further revealed the promising potential of these triblock copolymer micelleplexes for use in stimuli-responsive gene therapy.